A Rare Presentation of Metastasis of Prostate Adenocarcinoma to the Stomach and Rectum - Soe, Aye Min (J Gastric Cancer, 2014)
Prostate cancer is the second most common cause of cancer death in men in the United States. The most common sites of metastasis include the bone, lymph nodes, lung, liver, pleura, and adrenal glands, whereas metastatic prostate cancer involving the gastrointestinal tract has been rarely reported. A 64-year-old African-American man with a history of prostate cancer presented with anemia. He reported the passing of dark colored stools but denied hematemesis or hematochezia. Colonoscopy revealed circumferential nodularity, and histology demonstrated metastatic carcinoma of the prostate. Esophagogastroduodenoscopy showed hypertrophic folds in the gastric fundus, and microscopic examination revealed tumor cells positive for prostate-specific antigen. Bone scanning and computed tomography of the abdomen and pelvis did not show metastasis. It is crucial to distinguish primary gastrointestinal cancer from metastatic lesions, especially in patients with a history of cancer at another site, for appropriate management.